The Role of the Selective Thinking Strategy in Acquiring Learners’ Historical Concepts and Developing Their Knowledge - Negm, Moatasem Daoud; Al-Khatib, Aida (Journal of Tikrit University for Humanities, 2023)
The purpose of the research was to identify the role of the selective thinking strategy in acquiring the historical concepts of the learners and raising the level of their knowledge, and revealing the differences between the average scores of the history learners about the role of the selective thinking strategy in acquiring the historical concepts and developing their knowledge, which is due to the two variables: gender and academic year. In order to achieve this, the methodology based on description and analysis was adopted, and a questionnaire was designed of two parts: the first part dealt with statements that explain the role of this strategy in providing learners with concepts in the history course, and the second part explains its role in developing their knowledge. This questionnaire was applied to a sample of (184) history teachers, who were randomly selected from intermediate schools in the city of Kirkuk, Iraq. The results of the study showed that the selective thinking strategy plays a positive role in providing learners with historical concepts and increasing the degree of their knowledge and the grade variable in favor of the higher grade. Based on the results of the study, a number of proposals were formulated, including conducting research on the effectiveness of this method in developing scientific concepts.